Progress in understanding hormonal regulation during the postembryonic development of Helicoverpa armigera - Xiao-fan ZHAO (Journal of Integrative Agriculture, 2020)
Lepidoptera, with 0.16 million species, is the second largest order of insecta. This order includes silk worms, butterflies, and many agricultural pests. The cotton bollworm, Helicoverpa armigera (Hübner) is one of the pests in Lepidoptera that seriously harms cotton plant and other crops in China and other countries. This pest develops resistance to chemical insecticides rapidly. Bacillus thuringiensis (Bt) transgenic cotton plants are developed to control H. armigera population in the field. However, during the past years, the rapid evolution of Bt toxin resistance is observed in H. armigera in transgenic cotton fields. New approaches for the development of new environmentally friendly insecticides to control H. armigera have become necessary, and the molecular mechanisms underlying the development and physiological processes of this species need to be further understood. Considerable progress in the study of H. armigera development and physiology has been achieved in the last decade. This mini-review summarizes the main findings on the molecular mechanisms of hormonal regulation of the development of H. armigera to present new target genes for developing new approaches to control the pest.